Mastering Apache Maven 3 enhance developer productivity and address exact enterprise build requirements by extending Maven - Siriwardena, Prabath (Packt Publishing, 2014)
Annotation
Includes index. - Online resource; title from PDF title page (ebrary, viewed January 14, 2015)
Keywords: Application software -- Development; Project management -- Computer programs; Java (Computer program language); Logiciels d'application; Développement; Java (Langage de programmation); COMPUTERS; Programming Languages; Java; COMPUTERS; Internet; Application Development; Application software; Development; Project management; Computer programs